Pengembangan E-Modul Ekonomi Mata Pelajaran Ekonomi Bisnis Materi Pelaku Ekonomi Untuk Siswa Kelas X AKL 1 SMKN 2 Kediri - Kusnul Khotimah; Irmayanti, Elis; Surindra, Bayu (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
In research, it aims to result in e-Module economics for students of class X AKL 1 SMKN 2 Kediri. The method used in the development of this research is to develop the ADDIE model through five stages, but in the current research is limited to four stages. Validation test to three expert validators, namely material expert validator, media expert validator, and linguist validator. The validation test in this study was carried out through two stages. The results of the material expert validation test in the first stage received a score of 80.83% with good criteria, experiencing an increase in results in the second stage with a value of 90.83% with excellent criteria. In the validation test the first stage media media experts get a score of 75% with sufficient criteria, and the second stage increases with a value of 93.75% with excellent criteria. Furthermore, for the validation test linguists get a score with sufficient criteria of 65.63% and increase in the second stage by 87.5% with good criteria. e-Modules that are currently developed are considered quite effective in supporting classroom learning. Students can access on their respective gadgets, not spend too much internet quota, arranged systematically, and compiled based on e-Module development guidelines by the Directorate of High School Development.